Humor in professional coaching: a literature review and research agenda - Vendl, Adélka; Alvarado-Alvarez, Cristina; Euwema, Martin (Frontiers in Psychology, 2024)
Introduction: Extensive research has explored the incorporation of humor in therapy, revealing its potential positive effects on clients' mental well-being and personal growth. However, limited research exists on how coaching could benefit from humor as an intervention and how its utilization impacts the interaction processes and outcomes for both the coachee and coach. Therefore, our research focuses on the use and effects of spontaneous humor within professional dialogues. This paper aims to extract insights from academic literature on humor in adjacent fields and apply these insights to the context of coaching. Methods: This paper offers implications for coaching theory and practice, alongside a proposed research agenda. The initial phase involves analyzing reviews on humor in professional contexts, and coaching. Secondly, Following the PRISMA guidelines for review, we identified 13 empirical studies, which address the role of humor in counseling, psychotherapy, and mentoring. Results and discussion: Our findings suggest that humor serves as a valuable tool for establishing and deepening the working alliance, fostering adaptive coping mechanisms in clients, and enhancing the cognitive and behavioral process. Moreover, humor is shown to be advantageous for professionals in navigating challenging client relationships. These findings hold significance for the realm of coaching practice as well. In light of these insights, we propose the integration of humor use in education toolkits for coaching professionals.